2010
DOI: 10.1016/j.tet.2010.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Aminoarenethiolato-copper(I) as (pre-)catalyst for the synthesis of diaryl ethers from aryl bromides and sequential C–O/C–S and C–N/C–S cross coupling reactions

Abstract: a b s t r a c tA small library of 2-aminoarenethiolato-copper(I) (CuSAr) complexes was tested as (pre-)catalysts in the arylation reaction of phenols with aryl bromides. These copper(I) (pre-)catalysts are thermally stable, soluble in common organic solvents, and allow reactions of 6 h at 160 C with low catalyst loadings of 2.5 mol %. Among the (pre-)catalysts screened, 2-[(dimethylamino)methyl]benzenethiolato-copper(I) (1c) led to the best results and provided good to excellent yields of various substituted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 102 publications
(7 reference statements)
0
37
0
Order By: Relevance
“…We have also demonstrated that the use of aryl(TMP)iodonium tosylates is compatible with a combination of both sterically encumbered aryl electrophile and phenol nucleophile. The symmetrical, and highly sterically congested, 2,2′,6,6′‐tetramethyldiphenyl ether ( 2 ri ) has only been described in the literature on one other occasion, and in ∼2% yield by GCMS (Scheme ). The coupling of 1 r and 2 i proceeded in 52% isolated yield under our standard conditions to deliver 3 ri (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also demonstrated that the use of aryl(TMP)iodonium tosylates is compatible with a combination of both sterically encumbered aryl electrophile and phenol nucleophile. The symmetrical, and highly sterically congested, 2,2′,6,6′‐tetramethyldiphenyl ether ( 2 ri ) has only been described in the literature on one other occasion, and in ∼2% yield by GCMS (Scheme ). The coupling of 1 r and 2 i proceeded in 52% isolated yield under our standard conditions to deliver 3 ri (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…The symmetrical, and highly sterically congested, 2,2',6,6'-tetramethyldiphenyl ether (2 ri) has only been described in the literature on one other occasion, [13] and in~2% yield by GCMS (Scheme 2). The symmetrical, and highly sterically congested, 2,2',6,6'-tetramethyldiphenyl ether (2 ri) has only been described in the literature on one other occasion, [13] and in~2% yield by GCMS (Scheme 2).…”
Section: Communications Ascwiley-vchdementioning
confidence: 99%
“…For these reaction, many mechanisms are proposed and it is recognized that they are categorized into four classes . By examining the various reaction systems that have been developed so far, we can see that reaction products vary greatly depending on ligands, solvents, bases, and so on . Therefore the mechanistic discussion is still controversial even for the same experimental data …”
Section: Resultsmentioning
confidence: 99%
“…Transition metal‐catalyzed C−O bond formation with aryl halides and aromatic phenols is a powerful tool to prepare diarylethers ,. These products are commonly found in a variety of important compounds including a number of pharmaceuticals, agrochemicals, polymers, and life science . Therefore, the development of efficient methods for the synthesis of these essential compounds has achieved considerable attention in synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%